Does closure of chronic pilonidal sinus still remain a matter of debate after bilateral rotation flap?(N-shaped closure technique) - Khaled, M. Saad; Mohamed, M.S. Awad (Indian Journal of Plastic Surgery, 2006)
Background:Controversy still exists about the exact cause of pilonidal sinus either acquired or congenital, and also about what is the best surgical technique for the treatment of the disease. We successfully treated chronic pilonidal sinus with a new flap technique N-shaped bilateral rotation flap for closure of the defect.Materials and Methods:Thirty-two patients (30 men and two women) were treated by eccentric elliptical excision of the diseased tissues down to the postsacral fascia and closure of the defect with our flap [which is a random pattern flap], then a closed suction drain was placed at the base of the wound, with its tip being brought out in the gluteal region at least 5 cm lateral to the lower end of the suture line. Results: All our patients healed completely without recurrence during a period of average follow-up of two years. Mean hospital stay was 1.5 days (range 1-5 days). Mean time to complete healing was 11.9 days (range 6-18 days). Mean time off work was 13.7 days (range 10-21 days). Two patients had wound infection and one patient a partial breakdown. The recurrence rate was 0%.Conclusions:A tension-free suture via bilateral rotation flaps with a good suction at the button of the wound for drainage of blood from the bottom of the wound is the key to the success of repair without recurrence.
Keywords: N-shaped flap; pilonidal sinus; rotation flap